Self-Efficacy and Perceived Social Support as Predictors of Career Maturity among Twelfth-Grade Vocational High School Students - Reni Hadi Sulistio Ningsih; Pratidina Ekanesia; Prinska Damara Sastri (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study investigated the extent to which self-efficacy and perceived social support predict career maturity among twelfth-grade students at SMK Bintara Rancaekek. A quantitative cross-sectional correlational design was applied to the entire population of 53 students through total sampling. Data were collected using adapted and modified measures derived from the Career Decision-Making Self-Efficacy Scale, the Multidimensional Scale of Perceived Social Support, and the Career Development Inventory–Australian Version Short Form. Descriptive statistics, Pearson’s correlation, and multiple linear regression were employed for data analysis. The findings revealed that self-efficacy was a positive and statistically significant predictor of career maturity (β = .707, t = 7.246, p < .001). By contrast, perceived social support showed a positive but nonsignificant contribution (β = .150, t = 1.541, p = .130). The overall regression model was statistically significant, F(2, 50) = 27.603, p < .001, accounting for 52.5% of the variance in career maturity. These results suggest that students’ confidence in handling career-related tasks plays a more substantial role in career maturity than general perceptions of social support. Accordingly, vocational school career guidance should place greater emphasis on strengthening students’ confidence in career exploration, planning, decision-making, and problem-solving, while ensuring that social support is more specifically aligned with practical career-development needs.